2007
DOI: 10.1002/mrd.20780
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of pluripotency factors in the undifferentiated porcine inner cell mass and epiblast during in vitro culture

Abstract: Limited understanding of the importance of known pluripotency factors in pig embryonic stem cells (ESC) impedes the establishment and validation of porcine ESC lines. This study evaluated the expression of known mouse ESC and human ESC (hESC) pluripotency markers in in vivo inner cell mass (ICM) and in vitro-cultured undifferentiated porcine epiblast cells isolated from 8-day porcine blastocysts, primary cultures of epiblast-derived neuroprogenitor cells, and endoderm cells. The expression profile of common pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 59 publications
7
51
0
1
Order By: Relevance
“…2B), but examination of the microarray data of others (23,54) revealed that a similar phenomenon has been observed in reprogramming of murine and human cells. Finally, pNANOG was up-regulated during reprogramming, although it was already expressed in the parental PFF cells, an observation consistent with previous reports that NANOG is not a reliable marker for pluripotency in pig (32).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2B), but examination of the microarray data of others (23,54) revealed that a similar phenomenon has been observed in reprogramming of murine and human cells. Finally, pNANOG was up-regulated during reprogramming, although it was already expressed in the parental PFF cells, an observation consistent with previous reports that NANOG is not a reliable marker for pluripotency in pig (32).…”
Section: Discussionsupporting
confidence: 90%
“…Several genes associated with pluripotency and known to be expressed in the ICM of pig embryos, e.g., OCT4, SOX2, TDGF1 (CRIPTO) and TERT (32,33), were expressed only in the piPSC, and not in the founder PFF ( Fig. 2), providing evidence that reprogramming into a pluripotent state had been successful.…”
Section: Expression Of Pluripotent Genes In Pipscmentioning
confidence: 97%
“…OCT4/SOX2 proteins cooperate to activate the NANOG gene, suggesting that in pig blastocysts this interaction has not been established and therefore NANOG is not expressed. NANOG plays a critical role in establishing pluripotency in mammals [ 31 ]. In mouse blastocysts, NANOG is expressed in conjunction with OCT4 and SOX2 conferring pluripotent properties to the ICM [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of studies were merely confined to Nanog expression patterns by immunofluorescence and real time-PCR in porcine embryos and somatic stem cells, but the function of its role in cellular reprogramming and early embryo development by cooperating with other genes is still not defined. (Blomberg et al, 2008;Goel et al, 2008;Magnani and Cabot, 2008;Hall et al, 2009).…”
Section: Introductionmentioning
confidence: 99%